1999
DOI: 10.1007/s11886-999-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

Combination drug therapy for combined hyperlipidemia

Abstract: Combination therapy for hyperlipidemia, especially combined hyperlipidemia, may have advantages over single drug therapy, affording better improvement in lipoprotein risk factors and possibly better prevention of atherothrombotic events. Although preliminary experience has been gained using treatment combinations of niacin with statins, and fibrates with statins, few studies have focused on angiographic or clinical outcomes. Both of these treatment combinations increase the risk of drug-induced myopathy and rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Niacin monotherapy has beneficial effects on all lipoprotein classes, including LDL-C, very low-density lipoprotein cholesterol (VLDL-C) and lipoprotein (a). Depending on the dose and formulation, it is also associated with increases in HDL-C concentration of 25-28% [28]. Combination therapy including a statin with niacin therefore has the potential for additive beneficial effects across the lipid profile, particularly in patients requiring LDL-C reduction and an increase in HDL-C levels.…”
Section: Combination Therapy For Mixed Dyslipidemiasmentioning
confidence: 99%
See 1 more Smart Citation
“…Niacin monotherapy has beneficial effects on all lipoprotein classes, including LDL-C, very low-density lipoprotein cholesterol (VLDL-C) and lipoprotein (a). Depending on the dose and formulation, it is also associated with increases in HDL-C concentration of 25-28% [28]. Combination therapy including a statin with niacin therefore has the potential for additive beneficial effects across the lipid profile, particularly in patients requiring LDL-C reduction and an increase in HDL-C levels.…”
Section: Combination Therapy For Mixed Dyslipidemiasmentioning
confidence: 99%
“…It has been suggested that the incidence of myopathy with combination therapy may be lowered considerably if statin and niacin doses are limited [28], and this may also be the case for statin-fibrate combinations [56,57]. Thus, doses of each drug should be carefully titrated and kept to a minimum.…”
Section: Combination Therapy In Practicementioning
confidence: 99%
“…Niacin therapy produces beneficial effects on the entire lipoprotein profile, but its most dramatic effect is on HDL-C, increasing levels by 10% to 30% [30][31][32][33][34]. Niacin is currently available in a variety of chemical preparations, including immediate-release (regular/crystalline/IR), slowrelease (SR), and extended-release (Niaspan, KOS Pharmaceuticals, Miami, FL) forms.…”
Section: Nicotinic Acid (Niacin)mentioning
confidence: 99%
“…Fibric acid derivatives, employed primarily in the treatment of hypertriglyceridemia, can also increase levels of HDL-C by 6% to 20% [9,30]. Serum triglycerides (TG) and HDL-C are frequently inversely related, and fibrates are most effective in increasing HDL-C in patients with concomitant hypertriglyceridemia.…”
Section: Fibric Acid Derivatives (Fibrates)mentioning
confidence: 99%
See 1 more Smart Citation